Clinical Significance of Serum Albumin/Globulin Ratio in Patients With Pyogenic Liver Abscess - Zhang, Jia; Wang, Tao; Fang, Yi; Wang, Mengzhou; Liu, Wuming; Zhao, Junzhou; Wang, Bo; Wu, Zheng; Lv, Yi; Wu, Rongqian (Frontiers in Surgery, 2021)
Pyogenic liver abscess (PLA) remains a significant challenge for modern clinicians. Serum albumin/globulin ratio (AGR) can reflect the progress of many diseases. However, the clinical significance of AGR in PLA has not been evaluated. The aim of this study was to explore the effect of AGR on the clinical characteristic and prognosis in PLA patients. This retrospective study included 392 PLA patients who admitted to the First Affiliated Hospital of Xi’an Jiaotong University from January, 2007 to December, 2016. The medical records on admission were collected. Compared with the healthy controls and the patients with extraperitoneal infection or non-infectious liver disease, PLA patients had lower levels of AGR. The mean level of AGR in PLA patients was 1.02 ± 0.25. There were 179 (45.4%) patients with AGR > 1.02 and 213 (54.6%) patients with AGR ≤ 1.02. The baseline data and treatment plans of PLA patients with high or low AGR were comparative. However, PLA patients with a low AGR had higher body temperature, leukocytes and neutrophils, lower hemoglobin, poorer liver and coagulation function, larger abscess diameter, higher positive rate of pus culture and proportion of escherichia coli, and were more susceptible to multiple bacteria. Moreover, PLA patients with a low AGR had more complications, including systemic inflammatory response syndrome (SIRS), peritoneal effusion and pleural effusion. And it also need longer time for temperature normalization and hospital stay. In conclusion, PLA patients have lower AGR and lower AGR is associated with worse clinical manifestations, more complications and poorer prognosis. Thus, monitoring of AGR is of great clinical significance for evaluating the progress of PLA patients.